Measurement of the top quark mass in the dileptonic t(t)over-bar decay channel using the mass observables M-bl, M-T2, and M-blv in pp collisions at root=8 TeV - Sirunyan,AM; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A measurement of the top quark mass (Mt) in the dileptonic t¯t decay channel is performed using datafrom proton-proton collisions at a center-of-mass energy of 8 TeV. The data was recorded by the CMSexperiment at the LHC and corresponds to an integrated luminosity of 19.7 0.5 fb−1. Events are selectedwith two oppositely charged leptons (l ¼ e, μ) and two jets identified as originating from b quarks. Theanalysis is based on three kinematic observables whose distributions are sensitive to the value of Mt.An invariant mass observable, Mbl, and a “stransverse mass” observable, MT2, are employed in asimultaneous fit to determine the value of Mt and an overall jet energy scale factor (JSF). A complementaryapproach is used to construct an invariant mass observable, Mblν, that is combined with MT2 to measureMt. The shapes of the observables, along with their evolutions in Mt and JSF, are modeled by anonparametric Gaussian process regression technique. The sensitivity of the observables to the value of Mtis investigated using a Fisher information density method. The top quark mass is measured to be172.22 0.18ðstatÞ þ0.89 −0.93 ðsystÞ GeV.